The Effects of Cross-Cultural Competence and Social Support on International Students’ Psychological Adjustment: Autonomy and Environmental Mastery - Aldawsari, Norah Fahad; Adams, Katharine S.; Grimes, Lee Edmondson; Kohn, Steven (Journal of International Students, 2018)
This study investigated relationships between cross-cultural competence, social support, and international students’ psychological adjustment. Participants included 94 international students studying in the United States. The researchers conducted a series of standard multiple regression analysis to predict autonomy and environmental mastery as measured by the Ryff Scales of Psychological Well-Being (Ryff & Keyes, 1995). They found significant positive relationships between autonomy and cross-cultural competence as measured by the Intercultural Competence Scale (ICCS; Fantini & Tirmizi, 2006), and environmental mastery and social support as measured by the Multidimensional Scale of Perceived Social Support (MSPSS; Zimet, Dahlem, Zimet, & Farely, 1988). A significant negative  relationship was also found between length of residency in the host country, autonomy, and environmental mastery.